Epidural use in labour is not associated with an increased risk of maternal or neonatal morbidity when the second stage is prolonged. (4th September 2019) - Turner, Jessica; Flatley, Christopher; Kumar, Sailesh
Abstract : Background: Epidural analgesia increases length of labour and risk of operative delivery (caesarean or instrumental). Aim: This study aimed to assess the impact of epidural anaesthesia on maternal and neonatal adverse outcomes when the second stage of labour was prolonged. Methods: A retrospective cohort study of women delivering at term at the Mater Mother's Hospital, Brisbane between 2008 and 2017. Intrapartum, maternal and neonatal outcomes were assessed and dichotomised according to the presence of prolonged second stage of labour and further by epidural use. Prolonged second stage of labour was defined as: nulliparous women ≥3 h (with epidural) and ≥2 h (without); multiparous women ≥2 h (with epidural) and ≥1 h (without). Results: There were 48 352 women who met the inclusion criteria – 43 676 without and 4676 with prolonged second stage of labour. The overall epidural rate was 35.9%. Women with epidural had significantly lower odds of achieving a spontaneous vaginal birth and higher odds of an operative birth regardless of length of second stage. While rates of several adverse maternal and neonatal outcomes were higher when the second stage was prolonged, after adjusting for clinically relevant confounders, epidural use was not associated with increased odds of the majority of these adverse outcomes. Indeed, epidural use was associated with a significant reduction in the odds of obstetric anal sphincter injuries and reduced odds of neonatal acidosis in women with prolonged second stage. Conclusion: While epidural increases the risk of operative birth, this is not associated with an increase in adverse maternal or neonatal outcomes.